2004
DOI: 10.1111/j.1365-2605.2004.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted expression of intermediate filaments in the testis of rhesus monkey after experimental cryptorchidism

Abstract: Cytoskeletons in Sertoli cell play an important role in process of spermatogenesis. The expression and distribution of the intermediate filaments, vimentin, keratin and desmin, were studied in the Sertoli cells of the cryptorchid testis of rhesus monkey. Vimentin was localized in the perinuclear region of Sertoli cells of the normal testis. An intense increase in vimentin immunoreactivity was observed with appearance of disorganized staining in the Sertoli cells of the cryptorchid testes. Cytokeratin 18, a mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
41
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 35 publications
7
41
1
4
Order By: Relevance
“…Our observations of vimentin distribution from day-0 to 5 months of age and in mature bulls are in agreement with the previous studies in the bovine testis [10,15]. Similarly, as reported in rhesus monkeys [25] and in Japanese black bears [23], we have localized vimentin in a few interstitial cells and vascular walls of the bovine testes. Contrary to the observations in the Sertoli cells of the ground squirrel [30] and rat [11] and in agreement with previous reports in the ovine [5] and bovine [10], we were not able to observe any changes in the distribution of vimentin during the seminiferous cycle.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our observations of vimentin distribution from day-0 to 5 months of age and in mature bulls are in agreement with the previous studies in the bovine testis [10,15]. Similarly, as reported in rhesus monkeys [25] and in Japanese black bears [23], we have localized vimentin in a few interstitial cells and vascular walls of the bovine testes. Contrary to the observations in the Sertoli cells of the ground squirrel [30] and rat [11] and in agreement with previous reports in the ovine [5] and bovine [10], we were not able to observe any changes in the distribution of vimentin during the seminiferous cycle.…”
Section: Discussionsupporting
confidence: 81%
“…O u r f i n d i n g o f S e r t o l i c e l l p e r i n u c l e a r localization of the vimentin is consistent with previous reports in the rhesus monkey [25], rat [9,11,26], human [11,27,28], South American camelids [29], sheep [5], and bull [15]. Our observations of vimentin distribution from day-0 to 5 months of age and in mature bulls are in agreement with the previous studies in the bovine testis [10,15].…”
Section: Discussionsupporting
confidence: 81%
“…The T h e immunohistochemical localization of α-SMA and vimentin in the control testes in the present study followed the normal postnatal pattern described previously [5]. Different histological patterns of Sertoli cell immaturity have been reported in the human postpubertal cryptorchid testis [9], and the immature Sertoli cells of the cryptorchid rhesus monkey [8] and human [10] have demonstrated coexpression of vimentin, desmin, and cytokeratins. It has been suggested that local heat in vivo affects the fine structures of the Sertoli cells and the basement membrane of the seminiferous tubules of the rat testis [1].…”
Section: Discussionsupporting
confidence: 51%
“…Cryptorchid testes generally reveal different states of Sertoli cell immaturity [9] and demonstrate co-expression of vimentin, desmin, and cytokeratins [8,10]. However, the cytoskeletal alterations in the cryptorchid testis as compared to the normal testis during postnatal development are not yet understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation